2018
DOI: 10.1128/iai.00447-17
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum PfEMP1 Modulates Monocyte/Macrophage Transcription Factor Activation and Cytokine and Chemokine Responses

Abstract: Immunity to Plasmodium falciparum malaria is slow to develop, and it is often asserted that malaria suppresses host immunity, although this is poorly understood and the molecular basis for such activity remains unknown. P. falciparum erythrocyte membrane protein 1 (PfEMP1) is a virulence factor that plays a key role in parasite-host interactions. We investigated the immunosuppressive effect of PfEMP1 on monocytes/macrophages, which are central to the antiparasitic innate response. RAW macrophages and human pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 63 publications
1
20
1
1
Order By: Relevance
“…However, the response to ring‐stage iRBC‐EVs was not evaluated. We have recently shown that PfEMP1 located on the iRBC surface can specifically modulate the monocyte immune response to parasites (Sampaio, Eriksson, et al, ). However, to investigate whether the presence of PfEMP1 in ring‐stage iRBC‐EVs had a similar effect on monocytes, the optimal EV concentration for cell stimulation was first determined by flow cytometry to achieve the highest response (iRBC‐EV) to background (uRBC‐EV) signal (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the response to ring‐stage iRBC‐EVs was not evaluated. We have recently shown that PfEMP1 located on the iRBC surface can specifically modulate the monocyte immune response to parasites (Sampaio, Eriksson, et al, ). However, to investigate whether the presence of PfEMP1 in ring‐stage iRBC‐EVs had a similar effect on monocytes, the optimal EV concentration for cell stimulation was first determined by flow cytometry to achieve the highest response (iRBC‐EV) to background (uRBC‐EV) signal (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Namely, stimulus with PfEMP1‐negative iRBC‐EVs induced nearly three‐fold more gene expression changes compared to PfEMP1‐positive iRBC‐EVs and upregulated pathways involving “defence response,” “cellular response to cytokine stimulus,” and “response to stress,” which were not upregulated with the PfEMP1‐positive iRBC‐EVs. PfEMP1, when in the biologically relevant concentrations and cellular localisation of the iRBC surface, inhibits monocyte responses (Sampaio, Eriksson, et al, ). It is possible that PfEMP1 could also exert an immune modulatory effect on monocytes when delivered via EVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins function to assist the parasite to evade destruction by the host immune systems. 95,96 The PfEMP1 proteins were identified as the prime ligands responsible for cytoadherence and resetting. 97 They cause the infected RBCs of host tissues to sequester thus helping the parasite to circumvent clearance by the host's spleen.…”
Section: Neisseriamentioning
confidence: 99%
“…y por ende no desarrolla una inmunidad efectiva en comparación con las multigestantes 24 , además, la concentración de hormonas sexuales y el cortisol, tienden a disminuir a medida que aumenta la paridad 10,19,18 Fisiopatología de malaria placentaria Los eritrocitos infectados por Plasmodium spp., expresan un antígeno variante en su membrana, denominado -Plasmodium falciparum erythrocyte membrane protein 1-(PfEMP1) 25 , que facilita la adhesión de las células infectadas a receptores de condroitín sulfato A (CSA), presentes en la placenta 26 ; esta unión facilita el ingreso y secuestro del patógeno en el espacio intervelloso 27 , allí se desencadena una respuesta inmune pro-inflamatoria, mediada inicialmente por la liberación de TNF-α por parte de las células natural killer uterinas (NKu), que tiene un efecto químioatrayente sobre monocitos y macrófagos para amplificar la respuesta inmunitaria TH1 , en un intento por defender el contexto placentario contra la infección 19 .…”
Section: Malaria Y Paridadunclassified